Cultural values (power distance) impact on the stakeholders' engagement in organizing the Monsoon Cup international sailing event - Abdullah, Nawal Hanim; Hassan, Hamimah; Ali, Mass Hareeza; Abdul Karim, Muhammad Shahrim (Elsevier, 2014)
The aim of this research is to explore the unique cultural values (power distance) among the residents and organisers (government and Event Company) in organising the Monsoon Cup event. A qualitative research method was chosen for this study and data was collected by way of a number of in-depth semi-structured interviews through purposive and snowball samplings. The collected data was analysed using thematic content analysis. The findings from this study revealed that examining power distance issues had explained the relationship, perceived power and communication between the organisers and local residents.